Industrial training report: Perpustakaan Laman Hikmah, Universiti Teknikal Malaysia, Melaka / Nurhanis Sufiyah Salehan - Salehan, Nurhanis Sufiyah (Universiti Teknologi MARA, Negeri Sembilan, 2025)
An overview of my experience during my internship in the Laman Hikmah Library at UTeM, which took place from August 8, 2024, to January 17, 2025, is given in this industrial training report. This training, which aims to close the knowledge gap between theory and practical application in the academic library organization, is a significant component of my academic program. I was able to obtain firsthand information and expertise in a variety of library activities during my internship, such as digital resource management, cataloguing, shelving, and circulation services. During the internship, I was also exposed to customer service tasks, where I supported clients with queries, maintained the lending system, and enabled access to both physical and digital collections. The paper outlines the most important lessons learned, including how crucial organization, meticulous attention to detail, and efficient communication are to the seamless running of libraries. In summary, this industrial training prepared me for future career prospects by providing me with applicable skills and a wider understanding of how theoretical information is implemented in the industry.